SIMULASI PENYESUAIAN BEBAN PADA TRANSFORMATOR DI GARDU INDUK NUSA DUA - I Made Eko Adi Setiawan; I Wayan Rinas; I Wayan Arta Wijaya (Jurnal SPEKTRUM, 2020)
The rapid development in the South Kuta region has resulted in an increase in the demand for electricityenergy that must be supplied by the 150 kV Nusa Dua substation. An increase in the amount of load results in anincrease in the load that must be borne by the transformer. To prevent losses due to overload, a load adjustmentsimulation is performed on the transformer at the Nusa Dua Substation. Load flow simulation is done using ETAPsoftware with the subject of the power transformer load along with the load-feeders. The purpose of the simulation isto know the loading conditions and power loss of the Nusa Dua substation system. Furthermore, the transformerload adjustment scenario is designed, then simulated again with ETAP software to determine changes in the loadingconditions and the power loss in the Nusa Dua substation system. Simulation results in existing condition withnormal operation, transformer 1 load is 69,8% and transformer 3 is 71,8% with a total power loss of 14,1%. After 3planning scenarios for transformer load adjustment, scenario 2 is the bestl scenario in short term with the loading ontransformer 1 is 50,4%, transformer 2 is 45,9%, and transformer 3 is 45,1% with total power loss of 9,16%. While forthe long term, scenario 3 is recommended by adding a new transformer unit. Transformer 1 loading is 50,9%,transformer 2 is 45,9%, and transformer 3 is 45,1% with a total power loss of 9,24%.